Efficiency Comparison of the Cacao Intercropping Farming in Kolaka Regency - Nursalam Nursalam; Kabul Budiman; Campina Illa Prihantini; Hasbiadi Hasbiadi; Masitah Masitah (Agriekonomika, 2021)
The intercropping system is well-known for its extremely low risk of crop failure, its potential to overcome the risk of fluctuating product prices, and this system can save the production inputs. The study aims to compare the level of technical, allocative, and economic efficiency using the stochastic frontier production function model in the intercropping of cacao with annual crops with the pattern: cacao+coconut+patchouli; cacao+coconut+cashew; and cacao+coconut+banana. This research was conducted from March 2018 until April 2018 by determining the samples in the Kolaka Regency, which covered 17 sub-districts, taken from 3 sub-districts with purposive sampling. Each district was represented by 3 villages with purposive sampling. Each sub-district was represented by9 villages with total random samples of 270 respondents. The analysis used wasa technical, allocative, and economical efficiency analysis based on frontier analysis, with 270 respondents from 9 villages representing 3 sub-districts, using the random sampling method. The results discovered that the cacao intercropping farming system of cacao+coconut+patchouli had better technical, allocative, and economic efficiency values and was more feasible to cultivate compared to other patterns. The research results can be beneficial in developing cacao farmers’ performance relating to the annual intercropping crops. For academics, this research is expected to support the frontier production theory with the stochastic frontier efficiency model in cacao intercropping with annual crops.